2023
DOI: 10.1136/lupus-2022-000884
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the lupus low disease activity state as a treatment target in childhood-onset SLE

Abstract: ObjectiveTreat-to-target (T2T) strategies are advocated to improve prognosis in childhood-onset SLE (cSLE). Proposed T2T states include SLEDAI score of<4 (SLEDAI-LD), limited corticosteroid use (low-CS), and lupus low disease activity state (LLDAS). We sought to compare T2T states for their association with cSLE prognosis under consideration of relevant disease characteristics such as pre-existing damage, race and lupus nephritis (LN).MethodsLongitudinal data from 165 patients enrolled in the Cincinnati Lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Absence of nephritis was the only independent predictor of achieving LLDAS with one year of treatment [35]. Indeed, longitudinal data from 165 cSLE patients showed that LLDAS was the preferred T2T goal and minimized the risk of damage, although it was the most difficult to accomplish and sustain [36]. A Turkish study verified that almost 10% of cSLE had serological activity at the onset of remission, defined by modified definition of remission in SLE (DORIS) criteria.…”
Section: Treat-to-target Approachmentioning
confidence: 99%
“…Absence of nephritis was the only independent predictor of achieving LLDAS with one year of treatment [35]. Indeed, longitudinal data from 165 cSLE patients showed that LLDAS was the preferred T2T goal and minimized the risk of damage, although it was the most difficult to accomplish and sustain [36]. A Turkish study verified that almost 10% of cSLE had serological activity at the onset of remission, defined by modified definition of remission in SLE (DORIS) criteria.…”
Section: Treat-to-target Approachmentioning
confidence: 99%